Perancangan Desain Maskot Kabupaten Situbondo Dengan Pendekatan Design Thinking - Abdurrohman Abdurrohman; Addin Aditya; Rina Nurfitri (LPPM STIKI Malang, 2023)
The design of the Situbondo City mascot has carried out research on Situbondo Regency, because many people outside Situbondo do not know about Situbondo Regency, only the closest city. the author got some information about the mascot but many Situbondo people do not know what a mascot is and its function. Mascots are used not only to promote a city or area, but also to provide persuasive education about the city or area. The research method used in this design uses observation, interview, and questionnaire data collection techniques. The data collection is done online by distributing questionnaires to obtain accurate information and the results are used to achieve research objectives. a boat that is designed to live (anthrophomorphism) like a city icon by using a distinctive hat (odheng) in the form of a shell motif originating from the sea of Situbondo City and creating several poses from the mascot character of Situbondo Regency.